2017
DOI: 10.1007/s11205-017-1614-4
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Social Capital and Individualism–Collectivism in Europe

Abstract: The aim of the present study was to examine the relationship between social capital and individualism-collectivism in a sample of 50,417 individuals from 29 European countries using data from the European Social Survey Round 6 (2012). Social capital was measured in terms of generalized social trust and informal social networks; individualism-collectivism was operationalized via Schwartz's Openness to Change-Conservation value dimension.Results from a hierarchical linear modeling analysis showed that less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 67 publications
0
15
0
7
Order By: Relevance
“…30,52,53 Previous empirical research suggests that sources of social capital at the individual level can be found in people's immediate social surroundings, as well as their everyday social interactions. 54 In line with this, a recent empirical study in China suggests that social capital affects COVID-19 response mainly through facilitating collective actions and promoting public acceptance of and compliance with control measures in the form of trust and norms at the individual level. 55 These studies indicate how close and compatible social capital and collectivism are.…”
Section: Discussionmentioning
confidence: 90%
“…30,52,53 Previous empirical research suggests that sources of social capital at the individual level can be found in people's immediate social surroundings, as well as their everyday social interactions. 54 In line with this, a recent empirical study in China suggests that social capital affects COVID-19 response mainly through facilitating collective actions and promoting public acceptance of and compliance with control measures in the form of trust and norms at the individual level. 55 These studies indicate how close and compatible social capital and collectivism are.…”
Section: Discussionmentioning
confidence: 90%
“…In the opposite direction, we include a variable measuring self-perceived discrimination. The proxies for social capital used are in line with other studies based on ESS data [12,[42][43][44]. We further consider interaction variables between the covariates male and informal network/civic engagement.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Social capital often coexists within the relationship between farming households and farming organizations (Rahman et al 2020). This capital asset is represented by (1) financial expansion, (2) updated farming knowledge and skills, and (3) less collectivism (Deressa et al 2008;Beilmann et al 2018). In Vietnam, for instance, the emergence of more private farming cooperatives is prompted by the common objectives of members to obtain larger loans from agricultural banks, to share up-to-date farming techniques, and to collaborate in the production and marketing of agricultural products.…”
Section: Theoretical Frameworkmentioning
confidence: 99%